Single-particle dispersed silver powder with high specific surface area and high activity and preparation method of single-particle dispersed silver powder
By preparing high-specific high-active single-particle dispersed silver powder, the problems of bubble, shedding and sintering of existing silver powder when used in high-temperature silver paste are solved, and the tight bonding of the silver layer and high-yield etching effect are achieved.
Patent Information
- Application Number
- CN202510024290.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2045-01-07
AI Technical Summary
The existing high-active silver powder is prone to the problem of silver layer foaming and silver layer falling off when used in high-temperature silver paste. In the high-temperature sintering process, the sintering time is long and the temperature is high, resulting in the matt and yellowing of the silver layer, and poor etching or burrs during laser etching, and the product yield is low.
The high-specific high-active single-particle dispersed silver powder is used. The preparation method includes mixing silver nitrate with deionized water, adding triethanolamine solution, and stirring in a reactor, then adding vitamin C, dispersant I and dispersant II, continuing to stir and temperature control, and finally separating the silver powder from the solution, washing water and cleaning with water to obtain high-specific high-active single-particle dispersed silver powder.
This silver powder can be quickly fused and formed in the high-temperature sintering process. The silver layer has small resistance, the silver layer is closely combined with the substrate, and the sintered silver layer is bright white. It is suitable for high-temperature glass etching, piezoelectric ceramics and photovoltaic silver paste. The circuit yield after etching is high.
Smart Images

Figure CN119703112A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of silver powder in high-temperature silver paste, and specifically relates to a high-specific surface area and high-activity single-particle dispersed silver powder and a preparation method thereof. Background Art
[0002] With the development of the silver powder industry, more and more companies are involved in the technical research and development and production of silver powder. Various types and characteristics of silver powder have been developed, recognized by the market and completed large-scale production and application.
[0003] At present, the existing high-activity silver powder generally has the characteristics of relatively high specific surface area, high sintering activity, low tap density, relatively small silver powder particle size, and relatively wide distribution of silver powder particles. For example, Ag07 silver powder is a representative of this type, but this type of silver powder is not suitable for high-temperature silver paste, especially in high-temperature sintering process. The high-temperature silver paste prepared with this type of silver powder is prone to bubbling of the silver layer.
[0004] At present, the existing sintering-resistant silver powder generally has the characteristics of relatively small specific surface area, low sintering activity, slightly high tap density, and suitable silver powder particle size distribution, such as Ag02 silver powder and photovoltaic positive silver powder. However, although this type of silver powder is suitable for high-temperature sintering process, due to its low activity, the high-temperature silver paste using this type of silver powder generally requires a longer sintering time and a higher sintering temperature. If the sintering temperature is not enough or the sintering time is too short, the silver layer and the substrate are prone to loose bonding, resulting in the phenomenon of silver layer falling off, and the sintered silver layer is prone to matte and yellowing of the silver layer surface; and in certain production process conditions that require laser fine etching, due to the problems of too wide distribution of silver powder particles or poor dispersion of single silver powder particles, the silver layer circuits made using this type of silver powder high-temperature silver paste are prone to poor etching or etching circuit burrs, which ultimately leads to a relatively low product yield. Summary of the invention
[0005] In view of the problems existing in the prior art of high-activity silver powder and sintering-resistant silver powder used in high-temperature silver paste, the present invention provides a high-specific surface area, high-activity single-particle dispersed silver powder and a preparation method thereof. The prepared silver powder has high specific surface area and high activity, and presents a single-particle distribution state. The silver paste made with the silver powder is suitable for special high-temperature sintering processes, and the sintering process with the highest temperature peak greater than 700°C has unique advantages. The silver powder prepared by the present invention is suitable for the production of silver powder required for high-temperature silver paste in the silver powder industry, such as high-temperature glass etching silver paste, special piezoelectric ceramic silver paste and photovoltaic silver paste.
[0006] The purpose of the present invention is achieved through the following technical solutions: A method for preparing high specific surface area and high activity single-particle dispersed silver powder comprises the following steps: S1. Mix silver nitrate and deionized water in a mass ratio of 1:(5-7), stir and dissolve in reactor A, stir for 5 minutes, then add 80%-99.7% volume concentration of triethanolamine solution, the amount of triethanolamine solution added is 0.08%-0.2% of the mass of silver nitrate, continue stirring, and control the temperature at 47°C-50°C; S2, add deionized water, vitamin C, dispersant I and dispersant II to reactor B, wherein the mass ratio of the added mass of vitamin C to silver nitrate is 1:(1.2-1.5), the added amount of dispersant I is 12%-15% of the mass of silver nitrate, the added amount of dispersant II is 1%-3% of the mass of silver nitrate, the mass ratio of vitamin C to deionized water is 1:(5-18), after stirring and dissolving in reactor B, stir for 5 minutes, then add 80%-99.7% volume concentration of triethanolamine solution, the added amount of triethanolamine solution is 10%-25% of the mass of silver nitrate, continue stirring, and control the temperature at 47°C-50°C; The dispersant I is selected from polyvinyl pyrrolidone (PVP); the dispersant II is selected from modified polyethers; S3, adding the solution in reactor A to reactor B at a uniform rate, and stirring continuously, the adding process is controlled within 5min-15min, and stirring is continued for 10min-15min after all the solution is added to fully react, and then the silver powder and the solution are separated to obtain wet silver powder, and the wet silver powder is washed with deionized water, and when the conductivity of the wet silver powder is ≤30, alcohol with a volume concentration of 99% or more is added to remove water and wash, until the conductivity of the alcohol-mixed wet silver powder is ≤20; S4, dissolving the coating agent in alcohol with a volume concentration of 95% or more, the amount of the coating agent added is 0.1%-0.2% of the mass of silver nitrate, and the amount of alcohol with a volume concentration of 95% or more added is 3 times to 5 times the mass of the coating agent, and then adding the mixture to the alcohol-mixed wet silver powder obtained in the above step, stirring, and separating; The coating agent is selected from stearic acid, oleic acid, or a mixture of the two in any proportion; S5, drying the wet silver powder separated in the above step, and then performing air grinding to finally obtain a high specific surface area and high activity single particle dispersed silver powder, the particle size distribution of the silver powder is D 10 It is 0.81-0.85, D 50 It is 1.82-2.20, D 90 It is 2.70-2.91, the specific surface area is 0.43-0.48, and the tap density is 5.9-6.1.
[0007] In the present invention: The triethanolamine described in steps S1 and S2 acts as a surfactant in the synthesis process of silver powder, and is attached to the surface of silver powder particles to provide lipophilic and hydrophilic functional groups to the silver powder, so that the silver powder generated after the reaction is effectively suspended in the solution, achieving a better dispersion effect. At the same time, in the present invention, a weak alkaline solution such as triethanolamine is used to replace the existing strong alkaline solution or ammonia solution. After the reaction kettle A and the reaction kettle B, the pH value in the synthesis process of the silver powder reaction does not change much, thereby ensuring that the particle size of the silver powder is concentrated and dispersed in a single particle, and the temperature is controlled within the range described in the present invention, the purpose is to control the growth degree of the crystal in the reaction process of the silver powder, so that the activity of the silver powder is maintained in the required state. It can be seen from the SEM image that the surface of the silver powder synthesized by this method has more cracks and other dislocation defects. The silver powder of this structure is more active and can be quickly fused and formed under a high-temperature rapid sintering process, so that the body resistance of the silver layer is small.
[0008] The dispersant I described in step S2 is preferably PVP-K30S or PVP-K30. The function of this type of PVP dispersant is to increase the viscosity of the solution during the silver powder reaction process, and during the chemical reaction of the silver powder, the PVP resin adheres to the surface of the silver powder particles, so that the synthesized silver powder is in a single particle dispersed state.
[0009] The dispersant II described in step S2 is selected from modified polyethers, preferably hydroxy acrylic acid modified polyethers; the function of such modified polyether dispersants is to concentrate the particle size of the generated silver powder, and the silver powder is separated from particles in the solution without producing hard agglomerates; at the same time, the use of modified polyether high molecular weight dispersants can also increase the viscosity of the aqueous solution, increase the suspension performance of the silver powder particles, enhance the dispersion performance of the silver powder particles, and control the molecular weight of 20,000-50,000 so that the silver powder particles produced by the reaction are within the target range, achieving the expected experimental results.
[0010] The present invention also relates to a high specific surface area and high activity single particle dispersed silver powder, which is obtained by using the above-mentioned preparation method of a high specific surface area and high activity single particle dispersed silver powder, and the silver powder has a particle size distribution of D 10 It is 0.81-0.85, D 50 It is 1.82-2.20, D 90 It is 2.70-2.91, the specific surface area is 0.43-0.48, and the tap density is 5.9-6.1.
[0011] Compared with the prior art, the present invention has the following beneficial effects: 1. The method for preparing a high-specific surface area and high-activity single-particle dispersed silver powder of the present invention has large silver powder particles, is not prone to sintering and blistering problems, and has relatively high activity. The sintering of the silver layer circuit can be completed at a lower sintering temperature and a shorter sintering time, so that the silver layer and the substrate are tightly combined. In addition, the sintered silver layer presents a bright white color. In certain production process conditions requiring laser fine etching, the silver powder particles are concentratedly distributed and are in a single-particle dispersed state, so that the circuit yield after etching is very high, which is suitable for such special requirements.
[0012] 2. The high specific surface area and high activity single-particle dispersed silver powder described in the present invention can meet the current needs of photovoltaic silver powder. After the prepared silver powder is formulated into solar positive silver paste, it can meet the requirements of the production line and meet the current performance requirements of the photovoltaic industry for domestic silver powder. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention.
[0014] Figure 1 This is a scanning electron microscope image (10,000 times magnified) of the high specific surface area and high activity single-particle dispersed silver powder prepared in Example 1 of the present invention; Figure 2 This is a scanning electron microscope image (2,000 times magnified) of the high specific surface area and high activity single-particle dispersed silver powder prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0015] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0016] Embodiment 1: A method for preparing high specific surface area and high activity single-particle dispersed silver powder comprises the following steps: S1. Mix 12 kg of silver nitrate and 70 liters of deionized water in a reactor A, stir and dissolve, stir for 5 minutes, then add 10 g of 99% triethanolamine solution, continue stirring, and control the temperature at 47-50°C; S2. Add 10 kg of vitamin C to 60 L of deionized water in reactor B, add 1.5 kg of dispersant PVP-30S, add 120 g of 3W molecular weight hydroxy acrylic acid modified polyether (Zhejiang Weifa New Material Technology Co., Ltd.), stir and dissolve in the reactor, stir for 5 min, then add 1.5 kg of 99% triethanolamine solution, continue stirring, and control the temperature at 47-50 ° C; S3, adding the solution in reactor A to reactor B at a uniform rate, and stirring continuously, the adding process is controlled within 10 minutes, and stirring is continued for 10 minutes after all the solution is added to fully react, and then the silver powder and the solution are separated, and the conductivity of the wet silver powder is washed with deionized water to reach 30, and then 99% volume concentration of alcohol is added for dewatering and cleaning, and the conductivity of the alcohol-mixed wet silver powder reaches 20; S4, dissolving 12g of stearic acid as a coating agent in 60g of 99% alcohol by volume, then adding the mixture to the wet silver powder, stirring, and separating; S5, drying the wet silver powder separated in the above step, and then performing air grinding to finally obtain a high specific surface area and high activity single particle dispersed silver powder, the particle size distribution of the silver powder is D 10 is 0.83, D 50 It is 1.9, D 90 It is 2.8, the specific surface area is 0.47, and the tap density is 6.1.
[0017] Embodiment 2: A method for preparing high specific surface area and high activity single-particle dispersed silver powder comprises the following steps: S1. Mix 12 kg of silver nitrate and 60 liters of deionized water in a reactor A, stir and dissolve, stir for 5 minutes, then add 23 g of 99% triethanolamine solution, continue stirring, and control the temperature at 47-50°C; S2. Add 9 kg of vitamin C to 60 L of deionized water in reactor B, add 1.5 kg of dispersant PVP-K30, add 230 g of 3W molecular weight hydroxy acrylic acid modified polyether (Zhejiang Weifa New Material Technology Co., Ltd.), stir and dissolve in the reactor, stir for 5 min, then add 2 kg of 99% triethanolamine solution, continue stirring, and control the temperature at 47-50 ° C; S3, adding the solution in reactor A to reactor B at a uniform rate, and stirring continuously, the adding process is controlled within 10 minutes, and stirring is continued for 10 minutes after all the solution is added to fully react, and then the silver powder and the solution are separated, and the conductivity of the wet silver powder is washed with deionized water to reach 30, and then 99% volume concentration of alcohol is added for dewatering and cleaning, and the conductivity of the alcohol-mixed wet silver powder reaches 20; S4, dissolving 12g of coating agent oleic acid in 60g of 99% volume concentration alcohol, then adding it to the wet silver powder, stirring, and separating; S5, drying the wet silver powder separated in the previous step, and then performing air grinding to finally obtain a single-particle dispersed silver powder with high specific surface area and high activity; The particle size distribution of the silver powder is D 10 is 0.81, D 50 It is 1.82, D 90 It is 2.7, the specific surface area is 0.48, and the tap density is 6.1.
[0018] Embodiment 3: A method for preparing high specific surface area and high activity single-particle dispersed silver powder comprises the following steps: S1. Mix 12 kg of silver nitrate and 80 liters of deionized water in a reactor A, stir and dissolve, stir for 5 min, then add 17 g of 99% triethanolamine solution, continue stirring, and control the temperature at 47-50°C; S2. Add 8 kg of vitamin C to 60 L of deionized water in reactor B, add 1.8 kg of dispersant PVP-30S, add 330 g of 3W molecular weight hydroxy acrylic acid modified polyether (Zhejiang Weifa New Material Technology Co., Ltd.), stir and dissolve in the reactor, stir for 5 min, then add 2.8 kg of 99% triethanolamine solution, continue stirring, and control the temperature at 47-50 ° C; S3, adding the solution in reactor A to reactor B at a uniform rate, and stirring continuously, the adding process is controlled within 10 minutes, and stirring is continued for 10 minutes after all the solution is added to fully react, and then the silver powder and the solution are separated, and the conductivity of the wet silver powder is washed with deionized water to reach 30, and then 99% volume concentration of alcohol is added for dewatering and cleaning, and the conductivity of the alcohol-mixed wet silver powder reaches 20; S4, dissolving 6 g of stearic acid and 6 g of oleic acid in 60 g of 99% alcohol by volume, then adding the mixture to the wet silver powder, stirring, and separating; S5, drying the wet silver powder separated in the previous step, and then performing air grinding to finally obtain a single-particle dispersed silver powder with high specific surface area and high activity; The particle size distribution of the silver powder is D 10 is 0.85, D 50 It is 2.2, D 90 It is 2.91, the specific surface area is 0.43, and the tap density is 5.9.
[0019] Comparative Example 1: The difference between Comparative Example 1 and Example 1 is that ammonia water is used instead of triethanolamine, and the rest is the same as Example 1; The preparation of silver powder comprises the following steps: (1) In reactor A, 12 kg of silver nitrate and 70 liters of deionized water were mixed and stirred to dissolve, and then stirred for 5 minutes. Then, 3 g of 30% ammonia solution was added and stirred continuously. The temperature was controlled at 47-50°C. (2) In reactor B, add 10 kg of vitamin C to 60 L of deionized water, add 1.6 kg of dispersant PVP-30S, add 150 g of 3W molecular weight hydroxy acrylic acid modified polyether (Zhejiang Weifa New Material Technology Co., Ltd.), stir and dissolve in the reactor, stir for 5 min, then add 4.5 kg of 30% volume concentration ammonia solution, continue stirring, and control the temperature at 47-50 °C; (3) Add the solution in reactor A to reactor B at a uniform rate and stir continuously. The addition process is controlled within 10 minutes. After all the solution is added, continue stirring for 10 minutes to fully react. Then separate the silver powder and the solution, and wash the wet silver powder with deionized water until the conductivity reaches about 30. Then add 99% volume concentration of alcohol for dehydration and washing. The conductivity of the alcohol-mixed wet silver powder reaches below 20. (4) Dissolve 12 g of stearic acid as a coating agent in 60 g of alcohol, then add the mixture to the wet silver powder, stir, and separate; (5) drying the wet silver powder separated in the above step, and then performing air grinding to finally obtain a single-particle dispersed silver powder with high specific surface area and high activity; The particle size distribution of the silver powder is D 10 is 0.5, D 50 It is 1.9, D 90 It is 3.6, the specific surface area is 0.34, and the tap density is 5.8.
[0020] Comparative Example 2: The difference between Comparative Example 2 and Example 1 is that the dispersant such as polyvinyl pyrrolidone (PVP) is removed, and the other parts are the same as Example 1; The preparation of silver powder comprises the following steps: (1) In reactor A, 12 kg of silver nitrate and 70 liters of deionized water were mixed and stirred to dissolve, and then stirred for 5 minutes. Then, 10 g of 99% triethanolamine solution was added and stirred continuously. The temperature was controlled at 47-50°C. (2) Add 10 kg of vitamin C to 60 L of deionized water in reactor B, and add 150 g of 3W molecular weight hydroxy acrylic acid modified polyether (Zhejiang Weifa New Material Technology Co., Ltd.), stir and dissolve in the reactor, stir for 5 min, then add 1.5 kg of 99% triethanolamine solution, continue stirring, and control the temperature at 47-50 °C; (3) Add the solution in reactor A to reactor B at a uniform rate and stir continuously. The addition process is controlled within 10 minutes. After all the solution is added, continue stirring for 10 minutes to fully react. Then separate the silver powder and the solution, and wash the wet silver powder with deionized water until the conductivity reaches about 30. Then add 99% volume concentration of alcohol for dehydration and washing. The conductivity of the alcohol-mixed wet silver powder reaches below 20. (4) Dissolve 12 g of stearic acid as a coating agent in 60 g of alcohol, then add the mixture to the wet silver powder, stir, and separate; (5) drying the wet silver powder separated in the above step, and then performing air grinding to finally obtain a single-particle dispersed silver powder with high specific surface area and high activity; The particle size distribution of the silver powder is D 10 It is 0.52, D 50 It is 2.4, D 90 It is 4.9, the specific surface area is 0.21, and the tap density is 5.3.
[0021] Comparative Example 3: The difference between Comparative Example 3 and Example 1 is that the temperature range of the whole solution is different from the temperature control range of the whole solution in Example 1, and the others are the same as Example 1; The preparation of silver powder comprises the following steps: (1) In reactor A, 12 kg of silver nitrate and 70 liters of deionized water were mixed and stirred to dissolve, and then stirred for 5 minutes. Then, 10 g of 99% triethanolamine solution was added and stirred continuously. The temperature was controlled at 25-27°C. (2) In reactor B, add 10 kg of vitamin C to 60 L of deionized water, add 1.6 kg of dispersant PVP-30S, add 150 g of 3W molecular weight hydroxy acrylic acid modified polyether (Zhejiang Weifa New Material Technology Co., Ltd.), stir and dissolve in the reactor, stir for 5 min, then add 1.5 kg of 99% triethanolamine solution, continue stirring, and control the temperature at 25-27 °C; (3) Add the solution in reactor A to reactor B at a uniform rate and stir continuously. The addition process is controlled within 10 minutes. After all the solution is added, continue stirring for 10 minutes to fully react. Then separate the silver powder and the solution, and wash the wet silver powder with deionized water until the conductivity reaches about 30. Then add 99% volume concentration of alcohol for dehydration and washing. The conductivity of the alcohol-mixed wet silver powder reaches below 20. (4) Dissolve 12 g of stearic acid as a coating agent in 60 g of alcohol, then add the mixture to the wet silver powder, stir, and separate; (5) drying the wet silver powder separated in the above step, and then performing air grinding to finally obtain a single-particle dispersed silver powder with high specific surface area and high activity; The particle size distribution of the silver powder is D 10 is 0.75, D 50 It is 1.7, D 90 It is 2.6, the specific surface area is 0.24, and the tap density is 6.0.
[0022] Performance Test: The silver powder obtained in Example 1 was prepared into high-temperature glass silver paste 1, the silver powder obtained in Comparative Example 1 was prepared into high-temperature glass silver paste 2, the silver powder obtained in Comparative Example 2 was prepared into high-temperature glass silver paste 3, and the silver powder obtained in Comparative Example 3 was prepared into high-temperature glass silver paste 4. These pastes were then used on a glass substrate for printing and sintering, and etching was performed to test product performance. The specific indicators are shown in Table 1: Table 1: Sintering process performance, silver paste etching performance, and final circuit yield test
[0023] The silver powder obtained in Example 1 was prepared into high-temperature glass silver paste 1, the Zhongke copper Ag07 silver powder was prepared into high-temperature glass silver paste 5, and the Zhongke copper Ag02 silver powder was prepared into high-temperature glass silver paste 6. Then these pastes were used on a glass substrate for printing, sintering, and etching. Finally, the product performance was tested. The specific indicators are shown in Table 2: Table 2: Sintering process performance, silver paste etching performance, and final circuit yield test
[0024] The silver powder obtained in Example 1 was formulated into solar front silver paste A, the silver powder obtained in Comparative Example 1 was formulated into solar front silver paste B, the silver powder obtained in Comparative Example 2 was formulated into solar front silver paste C, and the silver powder obtained in Comparative Example 3 was formulated into solar front silver paste D. These pastes were then printed and sintered to test their performance. The specific indicators are shown in Table 3: Table 3: Printing and rapid sintering performance test of silver paste in solar production line
[0025] The silver powder obtained in Example 1 was formulated into solar front silver paste A, and compared with the production line solar silver paste. The electrical properties are shown in Table 4: Table 4: Electrical performance test of silver paste in solar production line
[0026] Results and Discussion: It can be seen from Tables 1 to 4 that the comprehensive effects of the embodiments are very good, the particle size distribution of the silver powder meets the requirements, the specific surface area reaches 0.47, and the tap density reaches 6.1.
[0027] From the comparison between Example 1 and Comparative Example 1, it can be seen that Figure 1 This is a 10,000-fold magnified scanning electron microscope image of the high specific surface area and high activity single-particle dispersed silver powder of Example 1. Figure 2 This is a 2,000-fold magnified scanning electron microscope image of the high-specific surface area and high-activity single-particle dispersed silver powder in Example 1. If other alkaline substances such as ammonia water are used to replace triethanolamine in reactor A and reactor B, the dispersing effect of triethanolamine will have an adverse effect on the dispersibility of the silver powder particles produced by the subsequent reaction, resulting in the final silver powder product not being able to reach the ideal state in terms of particle size distribution, specific surface area data and tapping. From the analysis of the data of Comparative Example 1, the overall silver powder has a small amount of large particle agglomeration. From the comparison of Example 1 and Comparative Example 2, it can be seen that if the dispersant PVP-K30S is removed, the final silver powder product also obviously shows the phenomenon of particle agglomeration. From the overall silver powder data performance of Comparative Example 2, relatively serious agglomeration occurs, resulting in the final silver powder product not reaching the ideal state in all indicators.
[0028] From the comparison between Example 1 and Comparative Example 3, it can be seen that if the reaction temperature in the scheme is changed, the specific surface area of the silver powder will decrease, affecting the subsequent sintering activity of the silver powder. From Comparative Example 3, it can be seen that as the temperature decreases, compared with Example 1, although the silver powder does not change much in particle size distribution and tap density, it has a significant decrease in specific surface area.
[0029] The silver powders obtained in Example 1 and Comparative Examples 1-3 were respectively formulated into high-temperature glass silver pastes. According to the various properties tested, the silver paste made from the silver powder in Example 1 meets the various process requirements, especially the sintering activity can meet the characteristics of high-temperature rapid sintering of glass-based materials, and meets the requirements of the production line in various subsequent test performances, such as circuit etching, with a very high yield. However, the silver pastes made from the various silver powders in Comparative Examples 1-3 all have various problems, because these silver powders have a relatively small specific surface area and poor activity, and the dispersibility of these silver powders is also poor, resulting in a relatively high defect rate in subsequent circuit etching.
[0030] Example 1 and the existing domestic high-activity silver powder and the existing sintering-resistant silver powder were respectively prepared into high-temperature glass silver paste. According to the various properties tested, the various properties of Example 1 met the requirements, while the existing domestic high-activity silver powder had the phenomenon of high-temperature sintering bubbles, which ultimately led to poor product circuit performance and unqualified products. In addition, the existing domestic sintering-resistant silver powder had poor sintering activity, which could not meet the high-temperature and fast sintering process, and caused problems such as poor etching in subsequent circuit etching.
[0031] The silver powders obtained in Example 1 and Comparative Examples 1-3 were respectively formulated into solar front silver pastes and tested for various properties. The silver pastes made from the silver powders in Example 1 met the production line requirements and were basically consistent with the production line pastes in the final electrical performance tests. However, the solar silver pastes prepared from the silver powders in Comparative Examples 1-3 had a high viscosity of the overall paste due to agglomeration problems, or could not be sintered quickly due to the activity problems of the silver powders, and could not meet the process requirements of the production line.
[0032] The above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a high specific surface area and high activity single particle dispersed silver powder, characterized in that: The following steps are involved: S1. Mix silver nitrate and deionized water in a mass ratio of 1:(5-7), stir and dissolve in reactor A, stir for 5 minutes, then add 80%-99.7% volume concentration of triethanolamine solution, the amount of triethanolamine solution added is 0.08%-0.2% of the mass of silver nitrate, continue stirring, and control the temperature at 47°C-50°C; S2, add deionized water, vitamin C, dispersant I and dispersant II to reactor B, wherein the mass ratio of the added mass of vitamin C to silver nitrate is 1:(1.2-1.5), the added amount of dispersant I is 12%-15% of the mass of silver nitrate, the added amount of dispersant II is 1%-3% of the mass of silver nitrate, the mass ratio of vitamin C to deionized water is 1:(5-18), after stirring and dissolving in reactor B, stir for 5 minutes, then add 80%-99.7% volume concentration of triethanolamine solution, the added amount of triethanolamine solution is 10%-25% of the mass of silver nitrate, continue stirring, and control the temperature at 47°C-50°C; The dispersant I is selected from polyvinyl pyrrolidone; the dispersant II is selected from modified polyethers; S3, adding the solution in reactor A to reactor B at a uniform rate, and stirring continuously, the adding process is controlled within 5min-15min, and stirring is continued for 10min-15min after all the solution is added to fully react, and then the silver powder and the solution are separated to obtain wet silver powder, and the wet silver powder is washed with deionized water, and when the conductivity of the wet silver powder is ≤30, alcohol with a volume concentration of 99% or more is added to remove water and wash, until the conductivity of the alcohol-mixed wet silver powder is ≤20; S4, dissolving the coating agent in alcohol with a volume concentration of 95% or more, the amount of the coating agent added is 0.1%-0.2% of the mass of silver nitrate, and the amount of alcohol with a volume concentration of 95% or more added is 3 times to 5 times the mass of the coating agent, and then adding the mixture to the alcohol-mixed wet silver powder obtained in the above step, stirring, and separating; The coating agent is selected from stearic acid, oleic acid, or a mixture of the two in any proportion; S5, drying the wet silver powder separated in the above step, and then performing air grinding to finally obtain a high specific surface area and high activity single particle dispersed silver powder, the particle size distribution of the silver powder is D 10 It is 0.81-0.85, D 50 It is 1.82-2.20, D 90 It is 2.70-2.91, the specific surface area is 0.43-0.48, and the tap density is 5.9-6.
1.
2. The method for preparing a high specific surface area and high activity single-particle dispersed silver powder according to claim 1, characterized in that: The dispersant I described in step S2 is selected from polyvinylpyrrolidone PVP-K30S or PVP-K30.
3. The method for preparing a high specific surface area and high activity single-particle dispersed silver powder according to claim 1, characterized in that: The dispersant II described in step S2 is selected from hydroxy acrylic acid modified polyether.
4. A high specific surface area and high activity single particle dispersed silver powder, characterized in that: The method for preparing a high specific surface area and high activity single-particle dispersed silver powder according to any one of claims 1 to 3 is used to obtain the silver powder, wherein the silver powder has a particle size distribution of D 10 It is 0.81-0.85, D 50 It is 1.82-2.20, D 90 It is 2.70-2.91, the specific surface area is 0.43-0.48, and the tap density is 5.9-6.1.
Citation Information
Patent Citations
Silver powder for printing size for solar cell electrodes and preparation process thereof
CN102921944A
Preparation method of seed-crystal-free particle-size-controllable submicron silver powder
CN116550985A
Ultrafine silver powder for HJT low-temperature silver paste and preparation method thereof
CN117282975A
Silver powder and preparation method thereof
CN118559018A
Silver powder and preparation method therefor
WO2023240825A1